PENGARUH TANGIBLE, RELIABILITY, RESPONSIVENESS, ASSURANCE DAN EMPATHY TERHADAP KEPUASAN PASIEN PENGGUNA BPJS DI RAWAT INAP RUMAH SAKIT SEMEN GRESIK (RSSG) - Aditya Narendra Wardhana; Deni Widiya Wati (Jurnal Ekonomi dan Manajemen, 2016)
Quality of service consisting of Tangible, Reliability, Responsiveness, Assurance, and Empathy and patient satisfaction is one unity that can not be separated. To realize patient's satisfaction, Hospital of Semen Gresik which oriented to health service is demanded to give good service quality for patients, so that society can live healthy and the goal health development can be achieved, it can be done by increasing the competence of hospital staff. This study aims to determine the influence of service quality on satisfaction BPJS’s patient at inpatient room of Semen Gresik Hospital (RSSG). Sample taking is using Probabiliyty Sampling technique, with kind of Simple Random Sampling. And the result show that tangibles and responsiveness variable had positive and significant effect on patient satisfaction while variable of reliability, assurance and empathy had no significant effect on patient satisfaction. Partially known that the dimension of responsiveness is the most influential variable on satisfaction of BPJS’s patient.